Education and outreach activities by the Antarctic Treaty Parties: topics and target audiences - Xavier, José C.; Mateev, Dragomir; Wilmotte, Annick; Peña-Aguirre, Andrea; Jupe, Julie; Ramos-García, Sonia; Abreu, José; Alfonso, Juan A.; Badhe, Renuka; Beck, Inga; Bialik, Robert J.; Carvalho, Andreia; et al. (Antarctic Science, 2024)
Abstract The relevance of education and outreach (E&O) activities about the Antarctic Treaty has been recognized at the Antarctic Treaty Consultative Meetings (ATCM) and at the Committee for Environmental Protection (CEP). This study examines the key topics and the target audiences detailed in papers submitted to the ATCM on E&O. Since the Antarctic Treaty entered into force in 1961, a total of 216 ATCM papers on E&O have been produced. The number of papers has increased substantially since the mid-1990s. ‘Science’ (76.9%) and ‘Wildlife/Biodiversity/Environment’ (75.5%) were the most addressed topics in these papers, while the ‘Public’ (81.0%) and those attending ‘Schools’ (69.0%) are the main target audiences. ‘Science’ in ATCM papers increased ~120-fold from 1961–1997 to 2015–2023, while ATCM papers discussing engagement with the ‘Public’ increased ~40-fold during the same period. ‘Climate change’ was first mentioned in 2006, and the number of papers per year increased fourfold by 2015–2023. This study shows the increasing interest in E&O through time, addressing key topics to relevant audiences related to the Antarctic region. From an educational perspective, attention should be paid to emerging topics (e.g. equity, diversity and inclusion), and the engagement of early-career professionals and educators should be made a priority.